Acculturation of Islam and Local Culture in the Sea Alms Tradition in the Coastal Community of Karangagung Village, Palang, Tuban - Himas Retna Kartika Putri; Prisiani Megantara Putri; Erlina Nur Susanti; Nurul Hakim (Konsultan Jurnal Ilmiah Indonesia, 2026)
This article aims to analyze the contribution of Generation Z in maintaining and enhancing This study aims to examine the implementation of the Sedekah Laut tradition, the process of acculturation between Islamic teachings and local culture, as well as the Islamic values contained within it in the coastal community of Karangagung Village, Palang District, Tuban Regency. This research employs a descriptive qualitative approach with a field research type supported by a literature study. Data were collected through interviews, observations, and documentation. The results show that the implementation of the Sedekah Laut tradition consists of several stages, namely preparation, communal prayers, tumpengan, social activities, and the peak event of the ritual of offering to the sea (larung sesaji). This tradition represents a form of acculturation between pre-Islamic local culture and Islamic teachings, which occurs gradually through adjustments in meaning and practice without eliminating the original cultural elements. In addition, this tradition contains Islamic educational values, including worship values reflected in prayer activities and expressions of gratitude to Allah SWT, moral values manifested in mutual cooperation and environmental awareness, and social values demonstrated through community participation that strengthens social relationships and fosters a sense of togetherness. Therefore, the Sedekah Laut tradition functions not only as a cultural heritage but also as a medium for instilling Islamic values and strengthening the social life of the community.